MicroRNAs in epilepsy: pathophysiology and clinical utility. Issue 13 (December 2016) - Henshall, David C; Hamer, Hajo M; Pasterkamp, R Jeroen; Goldstein, David B; Kjems, Jørgen; Prehn, Jochen H M; Schorge, Stephanie; Lamottke, Kai; Rosenow, Felix
Summary: Background: Temporal lobe epilepsy is a common and frequently intractable seizure disorder. Its pathogenesis is thought to involve large-scale alterations to the expression of genes controlling neurotransmitter signalling, ion channels, synaptic structure, neuronal death, gliosis, and inflammation. Identification of mechanisms coordinating gene networks in patients with temporal lobe epilepsy will help to identify novel therapeutic targets and biomarkers. MicroRNAs (miRNAs) are a family of small non-coding RNAs that control the expression levels of multiple proteins by decreasing mRNA stability and translation, and could therefore be key regulatory mechanisms and therapeutic targets in epilepsy. Recent developments: In the past 5 years, studies have found changes in miRNA levels in the hippocampus of patients with temporal lobe epilepsy and in neural tissues from animal models of epilepsy. Early functional studies showed that silencing of brain-specific miR-134 using antisense oligonucleotides (antagomirs) had potent antiseizure effects in animal models, whereas genetic deletion of miR-128 produced fatal epilepsy in mice. Levels of certain miRNAs were also found to be altered in the blood of rodents after seizures. In the past 18 months, functional studies have identified nine novel miRNAs that appear to influence seizures or hippocampal pathology. Their targets include transcription factors, neurotransmitter signalling components, and modulators of neuroinflammation. New approaches to manipulate miRNAs have been tested, including injection of mimics (agomirs) to enhance brain levels of miRNAs. Altered miRNA expression has also been reported in other types of refractory epilepsy and our understanding of how miRNA levels are controlled has grown, with studies on DNA methylation indicating epigenetic regulation. Biofluids (blood) of patients with epilepsy have shown differences in quantity of circulating miRNAs, implying diagnostic biomarker potential. Where next?: Recent functional studies need to be replicated to build a robust evidence base. The specific cell types in which miRNAs execute their functions and their primary targets have to be identified, to fully explain the phenotypic effects of modulating miRNAs. Delivery of large molecules such as antisense inhibitors or mimics to the brain poses a challenge, and the multi-targeting effects of miRNAs create additional risks of unanticipated side effects. Potential genetic variation in miRNAs should be explored as the basis for disease susceptibility. The latest findings provide a rich source of new miRNA targets, but substantial challenges remain before their role in the pathogenesis, diagnosis, and treatment of epilepsy can be translated into clinical practice.